ESG impact on IPO underpricing and short-term performance: Evidence from Nordic countries 2016-2021 - Räsänen, Amanda Karoliina (My University, 2024)
The importance of integrating environmental, social, and governance (ESG) factors into companies' operations has gained global attention in recent years. There is a large number of studies concentrating on the relationship between ESG and financial performance, but ESG and initial public offerings (IPO) are less studied. The previous ESG & IPO studies concentrate more on whether the disclosure before IPO affects underpricing, but not whether higher ESG disclosure leads to reduced underpricing. IPOs are characterized by information asymmetry between the company insiders and investors. When a company provides ESG information, it increases the information it provides to the public. Thus, when the ESG disclosure is higher, the information asymmetry is reduced. Additionally, the majority of the public information is incorporated into the IPO offer price. In addition to reduced information asymmetry, investors are increasingly considering ESG factors in their investment decisions. Investors consider ESG factors with traditional financial analysis when making investment decisions. This study examines the effect of the ESG score on rating an agency to the underpricing of an IPO. In addition, this thesis studies the short-term performance after IPO and do the ESG disclosure level affects that. The data is from Nordic markets from year 2016 to 2021. The study uses OLS regression to investigate the effect of the ESG score on underpricing and short-term performance after IPO. Additionally, this study tests each ESG pillar separately. The results of the study are mixed. Individual ESG pillars reduce the underpricing with a statistically significant result. However, the regression results are not statistically significant in the short-term performance, or the coefficients are, in economic terms, small. This suggests that the ESG factors do not have explanatory power on the short-term performance after the initial public offering, suggesting that ESG information is incorporated into the offer price, and thus, the effect on short-term performance after IPO is not significant.

Ympäristön, yhteiskuntavastuun ja hyvän hallintotavan (ESG) sisällyttäminen yritysten toi-mintaan on viime vuosina kasvattanut merkitystään maailmanlaajuisesti. Monet aikaisem-mat tutkimukset keskittyvät ESG-tekijöiden ja taloudellisen suorituskyvyn väliseen suhtee-seen, mutta ESG-tekijöitä ja listautumisia on tutkittu vähemmän. Aiemmissa ESG- ja listau-tumisantia koskevissa tutkimuksissa on keskitytty enemmän siihen, onko listautumista en-nen julkaistulla ESG tiedolla merkitystä alihinnoitteluun, eikä siihen, vaikuttaako yrityksen ESG taso alihinnoittelun. Listautumisanneissa tyypillistä on tiedon epäsymmetria yrityksen sisäpiirin ja sijoittajien välillä. Kun yritys jakaa ESG informaatiotaan, se lisää yleisölle tarjoamaansa tietoa. Näin ollen, kun julkisesti jaettavan informaation määrä kasvaa, tiedon epäsymmetria vähenee. Lisäksi suurin osa julkisesta tiedosta sisällytetään listautumisannin tarjoushintaan. Sen lisäksi, että tiedon epäsymmetria vähenee, sijoittajat ottavat yhä useammin huomioon ESG-tekijät sijoituspäätöksissään. Sijoittajat huomioivat yhä enemmän ESG faktorit perin-teisen rahoitusanalyysin ohella. Tässä tutkimuksessa tarkastellaan yrityksen ESG-pisteytyksen vaikutusta listautumisannin alihinnoitteluun. Lisäksi tutkitaan listautumisen jälkeistä suorituskykyä ja sitä, vaikuttaako ESG pisteytys siihen. Aineisto on pohjoismaisilta markkinoilta vuosilta 2016–2021. Tutki-muksessa käytetään OLS-regressiota, jolla tutkitaan ESG-pisteytyksen vaikutusta alihinnoit-teluun ja lyhyen aikavälin suorituskykyyn listautumisen jälkeen. Lisäksi testataan jokaista ESG:n kolmea pilaria erikseen. Tutkimuksen tulokset ovat ristiriitaisia. Yksittäiset ESG-pilarit vähentävät alihinnoittelua tilastollisesti merkitsevästi. Regressiotulokset eivät kuitenkaan ole tilastollisesti merkitse-viä lyhyen aikavälin suorituskyvyn osalta, tai vaikutus on todella pieni. Tämä viittaa siihen, että ESG-tekijöillä ei ole selittävää voimaa lyhyen aikavälin suorituskykyyn listautumisen jälkeen, mikä viittaa siihen, että ESG-tiedot sisällytetään tarjoushintaan ja väin ollen vaiku-tus lyhyen aikavälin suorituskykyyn listautumisen jälkeen ei ole merkittävä.
Keywords: fi=Laskentatoimi ja rahoitus|en=Accounting and Finance|; Master's Degree Programme in Finance